Towards The Four-Hour Rule: Impact of Observation Units and Emergency Medicine Specialists in an Indonesian Tertiary Hospital - Sulistio, Septo; Gani, Ascobat (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2025)
Emergency Department (ED) overcrowding is a global challenge. In response, the government of Indonesia mandates an ED Length of Stay (LOS) of ≤4 hours. This study aims to evaluate the impact of implementing an Emergency Department Observation Unit (EDOU) combined with an Emergency Medicine (EM) specialist-led disposition process on ED LOS at a national referral hospital in Indonesia. This was a retrospective, pre-post analysis comparing all ED visits in 2023 (pre-intervention, n = 26,282) with all visits in 2024 (post-intervention, n = 31,483). The primary outcome was the proportion of patients with an ED LOS ≤4 hours. Secondary outcomes included median ED LOS and the odds ratios (OR) for yellow zone patients achieving the ≤4-hour target based on the intervention period and the deciding physician's specialty. Following the intervention, the median ED LOS decreased from 16.4 hours to 8.0 hours (p-value =